2018
DOI: 10.1155/2018/7497619
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ammonia Adsorption on Directly Deposited Nanofibrous Carbon Films

Abstract: The ammonia adsorption on the nanostructured carbon thin film was significantly influenced by the choice of deposition temperature and deposition time of thin film synthesis. The thin films were prepared on Si/SiO2 substrates by chemical vapour deposition in Ar/C2H2 gas mixture using iron catalytic nanoparticles. The analysis of the grown layer by the scanning and transmission electron microscopy showed the transition from long multiwalled nanotubes (MWCNTs) to bamboo-like hollow carbon nanofiber structure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In our consideration of sensors based on CNTs, we should take into account that there are also sensors based on carbon nanofibers (CNFs) [ 104 , 153 , 154 , 155 ]. Since CNFs are cheaper than CNTs and semiconducting metal oxides, they become excellent candidates for sensing applications [ 154 ].…”
Section: Gas Sensors Based On Carbon Nanotubesmentioning
confidence: 99%
See 3 more Smart Citations
“…In our consideration of sensors based on CNTs, we should take into account that there are also sensors based on carbon nanofibers (CNFs) [ 104 , 153 , 154 , 155 ]. Since CNFs are cheaper than CNTs and semiconducting metal oxides, they become excellent candidates for sensing applications [ 154 ].…”
Section: Gas Sensors Based On Carbon Nanotubesmentioning
confidence: 99%
“…In the majority of articles published on the impact of relative humidity on the ammonia sensing properties of carbon nanotubes [ 24 ], carbon nanofibers [ 153 ], graphite oxide, and graphene oxide [ 92 ], it was reported that the sensor response increases with an increasing RH.…”
Section: Humidity and Its Impact On Sensing Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…ammonia (NH3), at rates as low as possible. The example of NH3 was chosen as ammonia is amongst the most dangerous gases, both for human health and environment [126]. The electrical properties of carbonaceous materials, especially the nanostructured ones [126], change under gas absorption, making them ideal materials for gas sensing applications.…”
Section: Gas Sensingmentioning
confidence: 99%